Edukasi Processing Film Radiografi Manual Pada Mahasiswa Baru Program Studi Radiologi - Utami, Lucky Restyanti Wahyu (Fakultas Teknik Universitas Cenderawasih, 2024)
Radiographic film processing is divided into conventional and digital. Conventional radiography film processing uses manual and automatic while digital radiography film processing uses computed radiography and digital radiography. Conventional radiographic film processing is carried out in a special room called a darkroom. As time goes by, Radiology Installations in various health services are starting to abandon conventional radiographic film processing and switch to digital. However, as a basic knowledge, radiology students must still know conventional radiographic film processing in order to know the development process of radiographic film processing. The aim of the education carried out for new students at the Widya Husada University Semarang Radiology Study Program is to increase knowledge of manual radiographic film processing and increase knowledge of the steps for using manual radiographic film processing. This educational activity is carried out using lecture and practical methods. Based on educational activities carried out for new students of the Radiology Study Program, the results showed that there was an increase in knowledge regarding manual radiographic film processing by 100% and there was an increase in knowledge regarding the steps for using manual radiography film processing by 97.8%.